Experimental studies of turbulent pulsating flow and heat transfer in a serpentine channel with winglike turbulators. (February 2022) - Wang, Chun-Sheng; Chen, Chieh-Chu; Chang, Wei-Che; Liou, Tong-Miin
Abstract: Particle Image Velocimetry and Infrared Thermography measurements are applied to explore the effect of quasi-triangular pulsatile flow inlet on active thermal-fluidic performance in a serpentine channel with innovative winglike turbulators. The novel turbulators are mounted in-line on two sidewalls of the channel with the attack angle ( α ), thickness to chord line ratio ( t/C ), and pitch to the channel hydraulic diameter ratio ( Pi/D H ) respectively fixed at 20°, 0.2, and 0.7. The Strouhal number ( St ) varies from 0 to 0.67 at a fixed Reynolds number ( Re ) of 10, 000. Relative to the steady-state case ( St = 0), the flow pulsation not only strengthens the Fujiwhara co-rotating vortices but also eliminates the corner vortex streams, leading to the overall Nusselt number ( Nu ¯ / Nu o ) enhancement by 13%. Moreover, both the Nu ¯ / Nu o and friction factor ( f ¯ / f o ) reveal the tilde-like trends with St, resulting in the highest Nu ¯ / Nu o of 5.2 and thermal performance factor of 1.39 at St = 0.67, which are higher than the previous best results for 10 ≤ f ¯ / f o ≤ 100 in the Nu ¯ / Nu o - f ¯ / f o diagram. Finally, by combing the present data with our previous steady state results, composite correlations of Nu ¯ / Nu o and f ¯ / f o versus Re, α, t/C, Pi/D H, and St are proposed. Highlights: Flow pulsation and winglike turbulators on heat transfer are firstly explored. Fujiwhara vortices are enhanced by pulsatile flow and increase Nu ¯ / Nu o by 13%. The highest TPF of 1.39 with Nu ¯ / Nu o of 5.2 is reported at St = 0.67. w p ' rms / U b ¯ p ¯ emerges as one of the major heat transfer mechanisms with R = 0.82. Correlations of Nu ¯ / Nu o and f ¯ / f o versus Re, α, t/C, Pi/D H, and St are proposed.